The Differential Impact of User Heterogeneity in Resource Management: A Case Study from Kerala - Jeena T Srinivasan (Working Paper No. 66, 2005)
This paper analyses the heterogeneous users decision to participate in comanagement, which is an institutional alternative proposed in the wake of state's failure in managing the Cochin estuarine fisheries in Kerala, India. Since a collective action under co-management require not only user's active participation in terms of their labor but also involve various types of organizational and managerial costs, the users were given the following choices on co-operation. Firstly, the users had the choice to contribute their labor in conservation activities, which would ensure sustainability of the fisheries. Secondly, they could make a voluntary contribution towards meeting the organizational costs of collective action. Thirdly, they could contribute in terms of labor as well as in monetary terms. Finally, they had the choice not to participate at all. Keeping in view the problems of free rider and adoption of stratagic behaviour by users some incentives were given for each of the above ways of co-operation. A multinomial logit analysis of the decision of about 369 sample fishermen to participate in co-management as defined above shows the differential impact of user heterogeneity in resource management. While heterogeneity in terms of the present legal status of the users motivate them for contributing their labor even in the absence of any additional economic incentives, heterogeneity in economic status and membership in formal organizations matters when it comes to making monetary payments. In addition to these, the overall optimism of the users' motivates them to both physically engage in conservation activities as well as make monetary payments. Adoption of strategic behaviors by at least some users cannot, however, be ruled out. On the whole it is seen that the heterogeneous fishermen's decision to participate depend upon their anticipation of the distribution of benefits from cooperation. However, one must be cautious that those who anticipate disproportionate benefit from co-operation are likely to take a lead role. Therefore, care must be taken to prevent them from deciding the rules of the game in such a manner that they are disproportionately in their favor